Membrane association and remodeling by intraflagellar transport protein IFT172. Issue 1 (December 2018) - Wang, Qianmin; Taschner, Michael; Ganzinger, Kristina; Kelley, Charlotte; Villasenor, Alethia; Heymann, Michael; Schwille, Petra; Lorentzen, Esben; Mizuno, Naoko
Abstract The cilium is an organelle used for motility and cellular signaling. Intraflagellar transport (IFT) is a process to move ciliary building blocks and signaling components into the cilium. How IFT controls the movement of ciliary components is currently poorly understood. IFT172 is the largest IFT subunit essential for ciliogenesis. Due to its large size, the characterization of IFT172 has been challenging. Using giant unilamellar vesicles (GUVs), we show that IFT172 is a membrane-interacting protein with the ability to remodel large membranes into small vesicles. Purified IFT172 has an architecture of two globular domains with a long rod-like protrusion, resembling the domain organization of coatomer proteins such as COPI-II or clathrin. IFT172 adopts two different conformations that can be manipulated by lipids or detergents: 1) an extended elongated conformation and 2) a globular closed architecture. Interestingly, the association of IFT172 with membranes is mutually exclusive with IFT57, implicating multiple functions for IFT172 within IFT. Cilia formation requires Intraflagellar transport (IFT) to move ciliary building blocks and signaling components into the cilium. Here authors use in vitro reconstitution and electron microscopy on IFT172 and reveal its ability to remodel large membrane surfaces into small vesicles.